Biomechanical Finite Element Method Model of the Proximal Carpal Row and Experimental Validation - Marqués, Rafael; Melchor, Juan; Sánchez-Montesinos, Indalecio; Roda, Olga; Rus, Guillermo; Hernández-Cortés, Pedro (Frontiers in Physiology, 2022)
The Finite Element Method (FEM) models are valuable tools to create an idea of the behavior of any structure. The complexity of the joints, materials, attachment areas, and boundary conditions is an open issue in biomechanics that needs to be addressed. Scapholunate instability is the leading cause of wrist pain and disability among patients of all ages. It is needed a better understanding of pathomechanics to develop new effective treatments. Previous models have emulated joints like the ankle or the knee but there are few about the wrist joint. The elaboration of realistic computational models of the carpus can give critical information to biomedical research and surgery to develop new surgical reconstructions. Hence, a 3D model of the proximal carpal row has been created through DICOM images, making a reduced wrist model. The materials, contacts, and ligaments definition were made via open-source software to extract results and carry on a reference comparison. Thus, considering the limitations that a reduced model could carry on (unbalanced forces and torques), the stresses that result in the scapholunate interosseous ligament (SLIL) lead us to a bones relative displacement, which support the kinematics hypothesis in the literature as the distal carpal row moves as a rigid solid with the capitate bone. Also, experimental testing is performed, successfully validating the linear strength values of the scapholunate ligament from the literature.